Community- and hospital-acquired Klebsiella pneumoniae urinary tract infections in Portugal : virulence and antibiotic resistance - Caneiras, Catia (2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).